BRAF Mutant Gastrointestinal Stromal Tumor: First report of regression with BRAF inhibitor dabrafenib (GSK2118436) and whole exomic sequencing for analysis of acquired resistance - Falchook, G.S. (Impact Journals LLC, 2013)
Activating oncogenic mutations of BRAF have been described in patients with gastrointestinal stromal tumor (GIST), but treatment of GIST with BRAF inhibitors and mechanisms of mediating the emergence of resistance in GIST have not been reported. Dabrafenib is a potent ATP-competitive inhibitor of BRAF kinase and is highly selective for mutant BRAF in kinase panel screening, cell lines, and xenografts. We report prolonged antitumor activity in the first patient with V600E BRAF-mutated GIST who was treated with a BRAF inhibitor. Whole exome sequencing performed in tumor tissue obtained at the time of progressive disease demonstrated a somatic gain-of-function PIK3CA mutation (H1047R) as well as a CDKN2A aberration, which may have contributed to eventual resistance to treatment.